Decision Support System for Accepting Social Assistance for the Program Keluarga Harapan (PKH) - Pangestu, Aji (International Journal of Informatics and Information Systems, 2022)
Cibangkong Village is one of the villages in Pekuncen District, Banyumas Regency. The number of recipients of PKH cards (Program Keluarga Harapan) is 253 families, data on KPM (Beneficiary Families) prospective recipients of BPNT (Non-Cash Food Assistance) are 278 families, and data for recipients of BLT (Direct Cash Assistance) village funds are 217 people (source Cibangkong Village in 2021). With so many recipients of this assistance, village officials encountered several obstacles, one of which was that the recipients were not eligible to receive assistance. This needs to be handled, one of which is by creating a Decision Support System that can assist village officials in overcoming these problems. Decision Support System (DSS) is a system that can assist a person in making accurate and targeted decisions. This study aims to produce a Decision Support System for receiving social assistance from the Family Hope Program (PKH) in Cibangkong village. This research uses the Multi Attribute Utility Theory (MAUT) method. The result of this research is that the making of a decision support system for receiving social assistance for the Family Hope Program (PHK) in Cibangkong village can be used as a tool by the Cibangkong village apparatus to consider the feasibility of prospective recipients of PKH social assistance. The criteria used in the Decision Support System for receiving social assistance from the Family Hope Program (PHK) in Cibangkong village are 12, namely income, savings, consuming meat, milk and chicken, ability to pay for treatment, education of the head of the family, building area, type of floor, house walls , latrines/WC, lighting sources, drinking water sources, and cooking fuel.